Development of p-Book and e-Book Based Modules in Batik Creation in Fine Arts Department - Sugito, Sugito; Atmojo, Wahyu Tri; Misgiya, Misgiya; Azis, Adek Cerah Kurnia (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2023)
This study aims to develop p-book and e-book-based modules that are valid, practical, and effective in the Archipelago Ornament Course and the Batik Craft Course in the Fine Arts Department. This research method used research and development with the 4-D development model (Four-D Models), namely: define, design, develop, and disseminate. The research instrument used a questionnaire with a Likert scale, while the data analysis technique consisted of validity data analysis, practicality data analysis, and effectiveness test data analysis. The results of this study indicated that: a) the validity value of the module was 79.25%, and the module was a pretty valid category; b) the value of the practicality of the module by students was 85.33%, and the module was included in the practical category in the learning process, and c) the average value of student activity (reading modules, asking questions, answering questions, and completing assignments) observed in the learning process and student learning outcomes was 82.81% which can be category as very active students and modules were category as effective. It showed that p-book and e-book-based modules were quite valid, practical, and effective in the learning process in the Archipelago Ornament Course and the Batik Craft Course in the Fine Arts Department, Faculty of Languages and Arts, Universitas Negeri Medan.